Social Impact of Technological Development Through Digitalisation In the Construction Industry - Gentjana REXHAJ (Communications of International Proceedings, 2024)
Digitalisation in the construction industry has a significant social impact. The introduction of digital technologies such as Building Information Modelling (BIM) is improving working conditions, creating new jobs and changing qualification requirements. The efficiency and quality of construction projects are optimised through more precise visualisation and better collaboration. Digitalisation also contributes to sustainability in the construction industry by reducing the use of resources and construction waste. However, challenges include the loss of traditional jobs and the risk of a digital divide, which can cause social inequalities. Targeted measures are therefore needed to ensure fair access to digital technologies. In addition, there are still gaps in knowledge regarding the impact on existing infrastructures and the standardisation of digital applications. The integration of BIM into the life cycle of infrastructure projects is of great importance for efficiency and sustainability. Further research is needed to exploit the full potential of digitalisation in the construction industry.
Keywords: Social impact; digitalisation; construction; technological development.